Relationship Between Nutritional Health and Academic Performance of School Going Children (Medical Forum Monthly, 2024)
Objective: The objective of the present study was to examine the significance of breakfast and nutrition with reference to academic performance of school aged children.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted in Lahore College for Women University, Lahore from March to April 2011.Materials and Methods: 368 children of grade 3-5, both boys and girls, from five private schools of Lahore were studied using purposive sampling. To see the nutritional level and academic performance of children, two self - constructed questionnaires, a) Child Nutrition and Performance Questionnaire and b) Child’s Performance Questionnaire were designed and used to collect the data.Results: The findings suggest that the children of regular breakfast group are high in academic performance as compared to irregular breakfast and no breakfast groups. The correlation between nutritional value of breakfast and academic performance was found to be significant.Conclusion: Considering the importance of children’s health, this study can show new directions to nutritionists, diet planners and researchers interested in health and well being of children.